O boato como simulacro: uma investigação sobre a comunicação no mercado financeiro - Martins, Valdir (2008)
This PhD thesis aims at the study of the meaning of rumor, defined as a constitutive element of communication with the ability of provoking alterations and influencing the performance of the financial market. It intends to show the changes capitalism has undergone throughout the historical and social evolutions of modern to postmodern civilization, focusing on the mediatization of the relations, and the adaptations and technical employments it has made use of to maintain the acceptance and the renovation of its practices. In our research, the concept of media culture is that of an organization based upon the mediation of social life through instruments of communication developed by new technologies, creating the predominance of the market as the single human universal and its unfoldings in the financial field. We propose a psychosocial analysis of the market and of the rumor as a vital element for its dynamics. The challenge for the research dwells in the fact that, as an unpredictable element in the performance of the financial market, the rumor has never received an appropriate attention, and there has never been a discussion of its importance to the conditioning of the oscillations, above all in the São Paulo Stock Exchange (Bovespa). The main hypothesis of this work is that, as a means of communication, the rumor has a preponderant role in the behavior of agents, directly influencing the performance and the oscillations of indexes, reflecting the capacity of reasoning in the construction of reality and demystifying the presumed rationality of markets. Our goal is to make a conceptual demonstration of the various historical passages and the adaptations of capital in the new infotechnical scenario, with special attention to the aspects of fluidity, liquidity and shallowness of actuality, supported by the dispute between time and space; attention will also be given to the influence of the behavior of participants in the alterations of market movements and to the new condition of the subject in this context of psychological and social changes. As to the approach of this work, we have chosen a theoretical and epistemological reflection. The methodological criteria have been based upon a bibliographical research guided by the concerns of critical analysis. We have also used case analysis, following closely the performance of ibovespa and the dollar, with the intention of revealing its tight connection to market oscillations. The structure of our argumentation has three parts: 1) the evolution of capitalism and its transformations; 2) the construction of market and its diverse traits; 3) the rumor and its function in the financial market. Our theoretical frame of reference is made up of authors such as Kapferer, Allport, Morin, Bauman, Baudrillard, Virilio and Trivinho, among others, and it is based upon the perspectives of the evolution of capitalism with foundation in the State; the construction of market identity; the surpassing of the subject; and the influence of rumor as a structuring component of the behavior of financial markets. This work intends to contribute to a more useful knowledge of the topic of communication in the business world and to bring into discussion the element of indetermination in the markets